2021
DOI: 10.1002/rmv.2299
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological interventions to prevent Covid‐19 disease: A rapid review

Abstract: Summary The aim of this rapid review was to determine the effectiveness of pharmacological interventions (excluding vaccines) to prevent coronavirus disease 2019 (Covid‐19) or reduce the severity of disease. A systematic search of published peer‐reviewed articles and non‐peer‐reviewed pre‐prints was undertaken from 1 January 2020 to 17 August 2021. Four randomised controlled trials (RCTs) and one non‐RCT were included; three trials (two RCTs and one non‐RCT) tested ivermectin with or without carrage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 17 publications
(79 reference statements)
0
5
0
Order By: Relevance
“…Urgent decision-making: RRs are valuable when policy-makers, healthcare providers or public health authorities face urgent decisions, such as responding to disease outbreaks, natural disasters or emerging health threats and need evidence to inform immediate actions 33 34. RRs can also guide clinical care decisions by synthesising available evidence for healthcare professionals requiring evidence for time-sensitive direct patient care decisions 35 36…”
Section: When Is It Appropriate To Do An Rr?mentioning
confidence: 99%
“…Urgent decision-making: RRs are valuable when policy-makers, healthcare providers or public health authorities face urgent decisions, such as responding to disease outbreaks, natural disasters or emerging health threats and need evidence to inform immediate actions 33 34. RRs can also guide clinical care decisions by synthesising available evidence for healthcare professionals requiring evidence for time-sensitive direct patient care decisions 35 36…”
Section: When Is It Appropriate To Do An Rr?mentioning
confidence: 99%
“…Ivermectin reduces the production of tumor necrosis factor (TNF)-alpha, IL-1 and IL-6 and numerous non-randomized, underpowered studies have demonstrated clinical efficacy in small studies [ 56 ]. However, the optimal dose, duration, and treatment population have not yet been identified and further studies are ongoing and it is not currently recommended as a treatment for COVID-19.…”
Section: Immunomodulators For Outpatientsmentioning
confidence: 99%
“…Standard preventive procedures including social distancing, regular hand sanitization, regular wiping of surfaces, quarantining and wearing of face masks have been adopted worldwide as the most effective methods of reducing the spread of the virus and limiting its morbidity and mortality [ 13 , 14 , 15 , 16 , 17 ]. While many treatments have been suggested to treat patients with COVID-19, only a few pharmacological therapies have been shown to be beneficial in the management of COVID-19 [ 18 , 19 , 20 , 21 , 22 ]. Therefore, many governments and health authorities, including the WHO, have been actively educating people to take preventive measures to decrease the spread of the virus [ 23 , 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%